2023
DOI: 10.3389/fgene.2022.1084937
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a TTN-associated immune prognostic model for skin cutaneous melanoma

Abstract: TTN is the most commonly mutated gene in skin cutaneous melanoma (SKCM). Tumor mutational burden (TMB) can generate new antigens that regulate the recognition of T cells, which will significantly affect the prognosis of patients. The TTN gene has a long coding sequence and a high number of mutant sites, which allows SKCM patients to produce higher TMB and may influence the immune response. It has been found that the overall survival (OS) of SKCM patients with TTN mutation was significantly higher than that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Survival analysis showed that patients with high risk TMB had a better prognosis, and patients in the high risk group had higher TTN and SETD2 expression. In colorectal cancer, cutaneous melanoma and thyroid cancer, TTN gene mutation is often used as a predictive biomarker to evaluate the immune microenvironment and prognosis [46][47][48]. SETD2 is a tumor suppressor whose mutation is prevalent in 7% of lung adenocarcinomas [49].…”
Section: Discussionmentioning
confidence: 99%
“…Survival analysis showed that patients with high risk TMB had a better prognosis, and patients in the high risk group had higher TTN and SETD2 expression. In colorectal cancer, cutaneous melanoma and thyroid cancer, TTN gene mutation is often used as a predictive biomarker to evaluate the immune microenvironment and prognosis [46][47][48]. SETD2 is a tumor suppressor whose mutation is prevalent in 7% of lung adenocarcinomas [49].…”
Section: Discussionmentioning
confidence: 99%